Analisis Pelaksanaan Supervisi Klinis dan Tindak Lanjut Pengembangan Guru di KB-TK ABA 17 Kota Malang - Najla Rafifah Hadi; Anisha Nuzula Ramadhani; Muhammad Bahrul Musthofa; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This research was conducted to explain and describe the implementation of clinical supervision and the forms of follow-up supervision at KB-TK ABA 17 Malang City. The study used a descriptive qualitative approach, in which the data were obtained through observations, interviews, and documentation. The collected data were then analyzed to obtain information. The results of the study indicate that the supervision carried out at KB-TK ABA 17 Malang City is directly supported by the principal through various mechanisms, such as semester supervision, daily monitoring, weekly evaluations, and gradual monitoring of students’ development. The follow-up actions from the implemented supervision are facilitated through the PKG and IGABA forums. One of the obstacles identified is the limited participant quota for teacher training or workshops. Through this clinical supervision, improvements in teachers’ competencies in teaching and learning activities can be observed.